Measurement of white matter fiber-bundle cross-section in multiple sclerosis using diffusion-weighted imaging. (May 2021) - Storelli, Loredana; Pagani, Elisabetta; Preziosa, Paolo; Filippi, Massimo; Rocca, Maria A
Background: When investigating white matter (WM) microstructure, the axonal fiber orientation should be considered. Constrained spherical deconvolution (CSD) is a diffusion-weighted imaging (DWI) method that estimates distribution of fibers within each imaging voxel. Objective: To study fiber-bundle cross-section (FC) as measured by CSD in multiple sclerosis (MS) patients versus healthy controls (HCs). Methods: DWI and three-dimensional (3D) T1 -weighted magnetic resonance imaging (MRI) were obtained from 45 MS patients and 45 HCs. We applied fixel-based morphometry analysis to assess differences of FC in MS against HCs and voxel-based analysis of fractional anisotropy (FA). Results: We found a significant widespread reduction of WM FC in MS compared to HCs. The decrease in FA was less extensive, mainly located in regions with high lesion occurrence such as the periventricular WM and the corpus callosum. Progressive MS patients showed a significant FC reduction in the right anterior cingulum, bilateral cerebellum, and in several mesencephalic and diencephalic regions compared to relapsing-remitting MS patients. Conclusion: The CSD method can be applied in MS for a fiber-specific study of WM microstructure and quantification of FC. Fixel-based findings offered greater anatomical specificity and biological interpretability by identifying tract-specific differences and allowed substantial abnormalities to be detected.